2008
DOI: 10.1007/s10157-008-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

Tubulointerstitial nephritis and IgA nephropathy in a patient with advanced lung cancer treated with long-term gefitinib

Abstract: A 52-year-old Japanese female was admitted to our hospital for microhematuria, proteinuria and progressive renal dysfunction. Two years prior to admission, she was diagnosed with lung adenocarcinoma and multiple bone and brain metastases, and was treated with gefitinib (250 mg/day). Treatment for 6 months induced partial response with 30% regression of the primary lung tumor, and resolution of metastatic tumors. After confirmation of the partial remission state, we performed percutaneous renal biopsy. Glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…22 This hypothesis was verified showing that in EBVtransformed B LCL ERK1/2 is hypo-phosphorylated in SPRY2 variant carriers and normal in the only family member, who tested negative for the variant. Moreover, as mentioned above, pERK1/2 is a strong transcriptional activator of SPRY2, 20,23,24 whereas its block causes SPRY2 transcriptional silencing. This tight transcriptional feedback explains the strong reduction observed in SPRY2 transcript, without apparent reduction in the protein levels.…”
Section: Association Of Mapkmentioning
confidence: 83%
“…22 This hypothesis was verified showing that in EBVtransformed B LCL ERK1/2 is hypo-phosphorylated in SPRY2 variant carriers and normal in the only family member, who tested negative for the variant. Moreover, as mentioned above, pERK1/2 is a strong transcriptional activator of SPRY2, 20,23,24 whereas its block causes SPRY2 transcriptional silencing. This tight transcriptional feedback explains the strong reduction observed in SPRY2 transcript, without apparent reduction in the protein levels.…”
Section: Association Of Mapkmentioning
confidence: 83%
“…3,4 Patients also should be evaluated for malignancy since adenocarcinoma is a known cause of pericardial effusion and nephritis. 5 In addition, uremia can generate a similar clinical picture. Evaluation of our patient revealed no signs of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, uremia can generate a similar clinical picture. Evaluation of our patient revealed no signs of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, both solid tumor such as renal cell cancer, lung cancer, pancreas cancer, and hematological malignancies such as Hodgkin's and non-Hodgkin's diseases, could induce IgA nephropathy, termed paraneoplastic IgA nephropathy [15,16]. Interestingly, a case is recently reported that IgA nephropathy occurs in gefitinib treatment for lung cancer [17].…”
Section: Discussionmentioning
confidence: 99%